Running with poles to increase training efficiency and reduce injuries - Tvznik, A.; Kutek, M. (New Studies in Athletics, 2014)
ABSTRACT Running makes significant demands on the musculoskeletal system, which is heavily strained as it absorbs up to three times the runner's body weight each time the foot strikes the ground. This strain often leads to injuries that compromise an athlete's training. The authors propose running with poles or Nordic Running, a means they tested on themselves, as a way to reduce orthopaedic strain and increase training efficiency. They start by comparing Nordic Running to cross-country skiing and Nordic Walking. This is followed by a report on an experiment showing that when running with poles the average maximum force on the feet is approximately 5% less and the pressure is redistributed to the front part of the foot compared to normal running, confirming the author's central claim. They then outline the case for including Nordic Running in the training programmes of athletes and make recommendations for the groups of athletes that could benefit from the practice. Also included are a description of the technique of running with poles and a brief presentation of ancillary exercises that can be done with the running poles.